2014
DOI: 10.2217/pmt.14.26
|View full text |Cite
|
Sign up to set email alerts
|

A Description of Clinical Characteristics and Treatment Patterns Observed within Prescribed Opioid Users in Germany and the UK

Abstract: While both populations were highly morbid populations largely initiated on weak opioids, chronic use was less common in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
4
14
0
Order By: Relevance
“…This means that patients with chronic diseases would be expected to have a slightly higher persistence on account of this factor. Besides the aforementioned comorbidities, depression was commonly observed in our study cohort (35.4% of patients), which supports results from previous studies, which indicate that chronic pain has physical and psychological effects such as depression, anxiety, or sleeping problems 8,19,22,40,44,45 . It also stresses the finding that high rates of psychiatric disorders and psychological distress occur in persons who regularly use prescribed opioids and therefore often require a greater level of management, care, and use of healthcare resources 11,19,22,40,46,47 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that patients with chronic diseases would be expected to have a slightly higher persistence on account of this factor. Besides the aforementioned comorbidities, depression was commonly observed in our study cohort (35.4% of patients), which supports results from previous studies, which indicate that chronic pain has physical and psychological effects such as depression, anxiety, or sleeping problems 8,19,22,40,44,45 . It also stresses the finding that high rates of psychiatric disorders and psychological distress occur in persons who regularly use prescribed opioids and therefore often require a greater level of management, care, and use of healthcare resources 11,19,22,40,46,47 .…”
Section: Discussionsupporting
confidence: 91%
“…According to the World Health Organization (WHO) 20-25% of the adult population suffer from chronic pain 2-5 , with prevalence increasing with age due to functional limitations and difficulty in performing daily activities in the elderly 6 . Consequently, the prescription of opioids has increased dramatically worldwide over the last few decades for patients suffering from both chronic non-malignant and cancer pain [7][8][9][10][11][12][13][14][15][16][17][18][19] . This trend is partially due to the growing interest in providing better pain management 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of long-term prescribing following tramadol initiation was 1.5% and 8.2% in France and Germany, respectively, although in Germany, the result was based on a smaller proportion of incident use where duration could be calculated (23% vs. 92%). The proportion of patients with long-term treatment in Germany was similar to the results from a previous study of opioids using data from IMS® Disease Analyzer in Germany [33]. Risk factors for long-term treatment appeared to include increasing age, a history of abuse or misuse and treatment with plain tramadol SR formulations.…”
Section: Discussionsupporting
confidence: 79%
“…4e8 Overall, approximately 18% of the population received an opioid prescription in 2012, which is a higher proportion than reported in other countries, although similar to some figures on the prevalence of chronic pain. 37 Many of these prescriptions will have been for acute pain and short-term use or at initiation of analgesic prescribing, 38 although we are unable to determine the extent of this and were unable to link to clinical data nationally. Epidemiological data from the USA and Denmark have shown that 3e5% of the population use prescribed opioids regularly for treatment of chronic pain.…”
Section: Discussionmentioning
confidence: 99%